Determination of instrument detection limit and method detection limit of varian 55B flame atomic absorption spectrometer for cadmium, chromium, copper, iron, lead, manganese and zinc using sips-10 and manual sample introduction methods. - Calawigan, Roland Joseph C. (2009.)
Determination of detection limits is an essential measure of performance for a quantitative laboratory, method or analyst. In this study, the Instrument Detection Limit (IDL) and Method Detection Limit (MDL) of F-AAS Varian 55B for cadmium, chromium, copper, iron, lead, manganese and zinc were determined using the SIPS-10 and manual sample introduction methods. For IDL determinations, EPA's SW-846 method (Test Methods for Evaluating Solid Waste and Physical/Chemical Methods) was employed for both sample introduction methods were deionized water analyzed for twenty time for three non-consecutive days. MDL determinations were done based on the definition given by the United STates Code of Federal Regulations (40 CFR part 136, Appendix B - Definition and Procedure for the Determination of the Method Detection Limit). In this procedure, MDL were estimated by calculating the standard deviation from the analysis of a standard solution containing the analyte with a concentration determined from the estimated detection limit, which was also analyzed for twenty times. Resultsshowed that for the determination of IDL, all of the elements have lowe values (Cd 0.000887 mg/L, Cr 0.00435 mg/L, Cu 0.000128mg/L, Pb 0.000742 mg/L, Mn 0.00399 mg/L, Cr 0.0150 mg/L, Cu 0.00222 mg/L, Fe 0.00913 mg/L, Pb 0.0217 mh/L, Mn 0.00132 mg/L, Zn 0.00445 mg/L). For MDL, the results showed variations for both the two sample introduction methods. The MDL values for cadmium, chromium, copper, iron, lead, manganese and zinc are 0.0374 mg/L, 0.0235 mg/L, 0.00203 mg/L, 0.0197 mg/L, 0.0805 mg/L, 0.00325 mg/L and 0.00686 mg/L in the manual method respectively and 0.0101 mg/L, 0.00280 mg/L, 0.197 mg/L, 0.00312 mg/L and 0.0103 mg/L in the SIPS10 method, respectively. Both methods have comparable precision for copper, iron, manganese and zinc determinations while SIPS-10 method is mpre precise for cadmium, chromium and lead analysis.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Cadmium; Chromium; Copper